The skill-specific impact of past and projected occupational decline - Lena Hensvik; Oskar Nordström Skans (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
Using very detailed register data on cognitive abilities and productive personality traits for nearly all Swedish males at age 18, we show that employment in the recent past has shifted towards skill-intensive occupations. Employment growth is monotonically skill biased in relation to this set of general-purpose transferable skills, despite the well-known U-shaped ("polarizing") relationship to occupational wage ranks. The patterns coexist because growing low-wage occupations tend to employ workers who are comparably skilled in these dimensions, whereas workers in declining mid-wage occupations instead have less of these general non-manual skills than suggested by their wages. Employment has primarily increased in occupations where workers have larger-than-average endowments of verbal and technical abilities and social maturity. Projections of future occupational decline and automation risks are even more skill-biased, but show similar associations to most of our specifc skill-measures. The most pronounced difference is that occupations relying on tolerance to stress are projected to decline in the coming decades.
Keywords: J21; J31; 330; Skills; Polarization; Future of Work